Independent Education Program for Teachers at SMPIT - Ibnu Jarir Dainuri; Rahmat Rosyadi; Santi Lisnawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Building a teacher's personality that includes spiritual and religious values is very important and fundamental, because he is responsible for the quality of education, he is the heir of the Prophet, he is an agent of improvement (ishlahul ummah) and the teacher is the front guard in realizing the ideals of independence. This research aims to analyze the implementation of the Independent Education Program for teachers at SMPIT Al Qalam Depok, West Java. The result of this analysis is the preparation of an Independent Education Concept to Strengthen Teachers' Islamic Personality Competencies at SMP-IT. This research is a type of qualitative research using methods, namely field research (field research). The primary data source from this research was obtained from field research at SMPIT Al Qalam Depok, West Java as well as other supporting books. Data collection techniques use observation, interviews and documentation, while analysis techniques use content analysis or content analysis. The results of research on Independent Education (tarbiyah dzatiyah) for teachers at SMPIT Al-Qalam Depok, West Java, found that there are a number of aspects that teachers have carried out in everyday life, especially in the school environment. A number of aspects of independent education are measured by the implementation of the following activities: 1) Regular Islamic studies week 2). Training held to explore a particular theme or skill 3). Tatsqif is an Islamic study to broaden insight and build perception 4). Al Yaum Ma'a al-Quran is a day's activity with the Koran. 5). Mabit is a worship program for spending the night together as a means of tazkiyatunnafs 6). Rihlah or recreation and 7). Evaluation of yaumiyah worship as a means of monitoring self-improvement commitments.